The road to guarantee the rights of the disabled and vulnerable groups in Peru based on the instruments of international protection - Solari Escobedo, Azucena Inés (2022)
The implementation of the Convention on the Rights of Persons with Disabilities posed a challenge for the countries that ratified this international instrument. In addition, Peru has signed the 100 Brasilia Rules, which requires a commitment, on the part of the courts of the signatory States. In the light of the foregoing, this article is designed to review the fulfillment of the respective good practices based on the public policies and on the inclusion of the Brasilia Rules, in the Judiciary, to guarantee the wellbeing of the vulnerable population, in particular of the persons with disabilities. To this effect, we have considered it pertinent to review the conceptual and normative framework, as well as some of the opinions of the Inter American Court of Human Rights and of the European Courts on the course to be followed to guarantee the rights of the disabled.